Targeting the gram-negative bacteria peptidoglycan synthase MraY as a new approach for monoclonal antibody anti-bacterial activity - Jun Cao; Fei Yi; Qiufeng Tian; Guanghui Dang; Wei Si; Siguo Liu; Shenye Yu (Taylor & Francis Group, 2017)
The use of antibiotics to target bacteria is a well-validated approach for controlling infections in animals and humans. Peptidoglycan biosynthesis is a crucial process in bacteria, and the conserved peptidoglycan synthase MraY is an attractive target for drug design. However, due to the lack of detailed MraY structural information, antibiotics targeting MraY have not yet been developed. In the present study, 2 hydrophilic regions of MraY from Escherichia coli were expressed as a fusion protein and used to raise a monoclonal antibody in mice. We confirmed that the MraY amino acid sequence PESHFSKRGTPT forms the core epitope recognized by the monoclonal antibody M-H11. Furthermore, our results show that M-H11 effectively controls Escherichia coli BL21 (DE3) plysS infection, both in vitro and in vivo. Our results may be of great value in the search for novel approaches used to control bacterial infections.